2019
DOI: 10.1142/s0218625x18501482
|View full text |Cite
|
Sign up to set email alerts
|

LINSEED OIL AS A NOVEL ECO-FRIENDLY CORROSION INHIBITOR OF CARBON STEEL IN 1 M HCl

Abstract: The extraction of linseed oil (LO) was realized by refluxing method. The extracted oil was identified by gas chromatography method coupled with mass spectrometry (GC-MS). In order to contribute to the protection of the environment, one contemplates to try on LO as a green corrosion inhibitor. The corrosion inhibition of LO was studied by weight loss and electrochemical methods. The obtained results showed that the LO is an effective inhibitor of the carbon steel corrosion in 1[Formula: see text]M HCl solution,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Indeed, R ct values significantly increase with PPD and achieve 319 Ω cm 2 at 10 −3 M. This performance is related to the creation of a barrier layer at the metal/solution interface which strongly inhibits local corrosion induced by chloride ions. The results showed that PPD molecules, instead of water molecules, act on the surface of the MS by adsorption at the steel/electrolyte interface as reported by some scientists [ 50 ].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, R ct values significantly increase with PPD and achieve 319 Ω cm 2 at 10 −3 M. This performance is related to the creation of a barrier layer at the metal/solution interface which strongly inhibits local corrosion induced by chloride ions. The results showed that PPD molecules, instead of water molecules, act on the surface of the MS by adsorption at the steel/electrolyte interface as reported by some scientists [ 50 ].…”
Section: Resultssupporting
confidence: 63%
“…The corresponding fit results obtained from the EIS plots for the PPD inhibitor at different concentrations are summarized in Table 3 . The double-layer capacitances, C dl , for a circuit comprising a CPE were determined by utilizing this formula [ 50 ]: …”
Section: Resultsmentioning
confidence: 99%
“…Recently, new studies succeeded in increasing the inhibition efficiency of green compounds. For instance, Gharda et al used linseed oil-based compounds as an eco-friendly corrosion inhibitor 8 . Ben Seddik et al used raw clay (Rhassoul) as a source of inhibitor 9 .…”
Section: Introductionmentioning
confidence: 99%